2011
DOI: 10.1371/journal.pone.0025758
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Transcript Initiation and Splicing as a Response to DNA Damage

Abstract: Humans are exposed to the DNA damaging agent, ionizing radiation (IR), from background radiation, medical treatments, occupational and accidental exposures. IR causes changes in transcription, but little is known about alternative transcription in response to IR on a genome-wide basis. These investigations examine the response to IR at the exon level in human cells, using exon arrays to comprehensively characterize radiation-induced transcriptional expression products. Previously uncharacterized alternative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 59 publications
4
67
0
Order By: Relevance
“…Two key DNA damage sensors, the DSB sensor MRE11 and the DNA nick sensor PARP genes (De Vos et al, 2012), were regulated by alternative splicing, while RNA-Seq highlighted the modulation of chromatin remodelling genes required for disruption of the nucleosome-DNA interactions and stimulating DNA repair (van Attikum and Gasser, 2005). The expression of alternative gene isoforms was identified as a mechanism of DNA damage response in human cells and similarly the RNA-Seq results clearly indicate that this mechanism is used as a response to Tdp1α depletion in M. truncatula (Sprung et al, 2011). Moreover, Sanchez-Pons et al (2011) identified changes in the expression of genes related to RNA processing, which predominantly occurs in the nucleolus, in maize embryos exposed to camptothecin.…”
Section: -Test) (B)mentioning
confidence: 83%
“…Two key DNA damage sensors, the DSB sensor MRE11 and the DNA nick sensor PARP genes (De Vos et al, 2012), were regulated by alternative splicing, while RNA-Seq highlighted the modulation of chromatin remodelling genes required for disruption of the nucleosome-DNA interactions and stimulating DNA repair (van Attikum and Gasser, 2005). The expression of alternative gene isoforms was identified as a mechanism of DNA damage response in human cells and similarly the RNA-Seq results clearly indicate that this mechanism is used as a response to Tdp1α depletion in M. truncatula (Sprung et al, 2011). Moreover, Sanchez-Pons et al (2011) identified changes in the expression of genes related to RNA processing, which predominantly occurs in the nucleolus, in maize embryos exposed to camptothecin.…”
Section: -Test) (B)mentioning
confidence: 83%
“…In addition to mediating precursor messenger RNA (mRNA) processing, spliceosomal proteins have been shown to influence histone modifications via physical interactions with Polycomb group proteins, 13 activate transcription through direct and indirect regulation of RNA polymerase elongation, 14,15 and coordinate aspects of cellular response to DNA damage. 16,17 The mutual exclusivity of splicing pathway mutations indicates that these alterations are either functionally redundant or that more significant disruption of canonical or noncanonical spliceosome activity is not tolerated by the cell.…”
Section: Rna Splicingmentioning
confidence: 99%
“…In ex vivo studies, several protocols have been used such as cultured peripheral blood mononuclear cells (PBMC) (Dressman et al 2007;Meadows et al 2008Meadows et al , 2010Sprung et al 2011;Boldt et al 2012;Knops et al 2012;Riecke et al 2012;Macaeva et al 2016), cultured whole blood diluted with media Brzoska andKruszewski 2015, Abend et al 2016) or undiluted whole blood (Manning et al 2013). However, none of these studies have addressed the role of blood culture methods during the incubation time at 37 C following radiation exposure.…”
Section: Introductionmentioning
confidence: 99%